Teacher Professionalism Development in Community Based Research-Based Multicultural Islamic Education Learning - Lia Nur Atiqoh Bela Dina; Fita Mustafida (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
Learning Islamic Education by integrating multicultural values is indispensable. The presence of multicultural education has an important role in improving and providing solutions to various religious problems. It's just that teachers still have difficulty in integrating multicultural values in learning. There needs to be a development of teacher professionalism in terms of learning based on multicultural values, because the increasing professionalism of teachers will have an effect on improving the quality of learning both processes andresults. The method of community service used is the Community Based Research (CBR) method with RRA(Rapid Rural Appraisal) technique. Devotional activities through the multicultural PAI learning model raise awareness of teachers or assisted groups to develop their professionalism and competence in organizing innovative and quality learning.